Association between maternal cholesterol level during pregnancy and placental weight and birthweight ratio: data from the Japan Environment and Children's Study - Naomi Mitsuda; Masamitsu Eitoku; Keiko Yamasaki; Naw Awn J-P; Mikiya Fujieda; Nagamasa Maeda; Narufumi Suganuma; on behalf of the Japan Environment and Children's Study (JECS) (BMC, 2023)
Abstract Background Placental weight to birthweight ratio (PW/BW ratio), or its inverse, is used as an indicator of placental efficiency. Past studies have shown an association between an abnormal PW/BW ratio and adverse intrauterine environment, however, no previous studies have examined the effect of abnormal lipid levels during pregnancy on PW/BW ratio. We aimed to evaluate the association between maternal cholesterol levels during pregnancy and placental weight to birthweight ratio (PW/BW ratio). Methods This study was a secondary analysis using the data from the Japan Environment and Children's Study (JECS). 81 781 singletons and their mothers were included in the analysis. Maternal serum total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) levels during pregnancy were obtained from participants. Associations between maternal lipid levels and placental weight and PW/BW ratio were assessed by regression analysis using restricted cubic splines. Results Dose-response relationships were observed between maternal lipid level during pregnancy and placental weight and PW/BW ratio. High TC and LDL-C levels were associated with heavy placental weight and high PW/BW ratio, i.e., inappropriately heavy placenta for birthweight. Low HDL-C level was also associated with inappropriately heavy placenta. Low TC and LDL-C levels were associated with low placental weight and low PW/BW ratio, i.e., inappropriately light placenta for birthweight. High HDL-C was not associated with PW/BW ratio. These findings were independent of pre-pregnancy body mass index and gestational weight gain. Conclusions Abnormal lipid levels such as elevated TC and LDL-C, and low HDL-C level, during pregnancy were associated with inappropriately heavy placental weight.